2018
DOI: 10.1177/1753425918792298
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of microRNAs and their predicted targeting mRNAs expression in RAW264.7 macrophages infected with Omp25 mutant Brucella melitensis

Abstract: Brucellosis is a worldwide zoonosis caused by Brucella species and represents a serious threat to both human and animal health. Omp25 is an important immunogenic and protective antigen in Brucella species; however, the functional mechanism of Omp25 in macrophages has not yet been elucidated. Here, we constructed a Brucella melitensis omp25 deletion mutant (M5-90-Δ omp25) and performed microRNA (miRNA) profiling of infected RAW264.7 cells. Eight differentially expressed miRNAs ( mmu-miR-146a-5p, mmu-miR-155-5p,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Further, mir-5126 was downregulated in macrophage cells infected by the intracellular bacterial pathogen Brucella melitensis (Zhu et al, 2018), and was also downregulated in mice with an intestinal inflammation response (Yao et al, 2020). Finally, mir-H17 was upregulated in viral infections, such as in mice trigeminal ganglia infected by herpes simplex virus (HSV) (Du, Han, Zhou, & Roizman, 2015), or in the spleens of chickens co-infected with two herpesviruses, the pathogenic strain MDV1 and the vaccine strain HVT (Goher et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, mir-5126 was downregulated in macrophage cells infected by the intracellular bacterial pathogen Brucella melitensis (Zhu et al, 2018), and was also downregulated in mice with an intestinal inflammation response (Yao et al, 2020). Finally, mir-H17 was upregulated in viral infections, such as in mice trigeminal ganglia infected by herpes simplex virus (HSV) (Du, Han, Zhou, & Roizman, 2015), or in the spleens of chickens co-infected with two herpesviruses, the pathogenic strain MDV1 and the vaccine strain HVT (Goher et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Out of nine DEmir families, seven have been linked to biological functions relating to immune responses and/or host-parasite interactions (Table 1). Specifically, mir-11987, mir-164, mir-6240, mir-11980, mir-5126, mir-6937-5p and mir-H17 have been found to be differentially expressed either during pathogenic infections by nematodes, bacteria or viruses, or during cancer or inflammation-related disorders (Abu-Izneid et al, 2021;Escuin et al, 2020;Goher, Hicks, & Liu, 2013;Ma et al, 2016;Ning & Sun, 2020;Palumbo, Faucz, Azevedo, Xekouki, & Iliopoulos, 2013;Wu, Ning, & Sun, 2021;Wu et al, 2020;Yao et al, 2020;Zhao, Hou, & Yan, 2022;Zhu et al, 2018).…”
Section: Functional Analysis Of Demirsmentioning
confidence: 99%
“…MiRNAs have been proven to participate in brucellosis immunopathogenesis. Our previous studies found that the autophagic pathway associated miRNAs, mmu-miR-146b-5p and mmu-miR-149-3p was up-regulated and down-regulated in RAW264.7 macrophage cells infected with B.melitensis M5-90 mutant strain, respectively ( 18 , 19 ). In B.melitensis -infected goat fibroblasts, we found that miR-744, miR-29a-5p and miR-193b-5p play pleiotropic roles in inflammatory and immune responses ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that infecting RAW264.7 macrophages with B. melitensis Δ Omp25 altered the expressions of miR-149-3p and miR-146a-5p, and the target genes of miR-149-3p were related to the host immune responses, autophagy and phagosome maturation ( 18 ). After infection with B. melitensis M5-90 Δper, the increased expression of miR-146b-5p inhibited autophagy activation in RAW264.7 cells ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effective elimination of pathogens depends on several signaling pathways, such as Toll-likereceptor (TLR) signaling; many of these are regulated by miRNA (27). MiR-671, as a biomarker, is involved in macrophage immune signal transduction in the early stage of the inflammatory response (28)(29)(30). Activated macrophages release various immune regulatory factors and reduce the expression of miR-671 (31).…”
Section: Mechanisms Of Mir-671 Regulating the Inflammatory Responsementioning
confidence: 99%